Toxidez por cobre: reflexos na qualidade de sementes e no desenvolvimento inicial de aveia preta - Comiran, Mariane (2017)
in the soill elevated over the years through anthropogenic actions such as the application of manure and cupping fungicides. As a reflection of these increases the establishment and development of plants grown in these environments can be limited and compromised. Considering the particularities of the different species in resisting and completing their cycle on these conditions this work aimed to evaluate Cu interference on the establishment and initial growth of black oats. The treatments were set up in 5x2 bifactorial, with five concentrations of copper (0, 60, 120, 180, 240 μM) and two sub lots (vigor levels). Thus, analyzes of physiological parameters of black oat seedlings and plants from two sub lots, one artificially aged and another not, both originated from a single lot, were performed. Two experiments were carried out; in the first one, physiological parameters were evaluated which comprise the establishment capacity of the seedlings such as the first count and germination test in B.O.D germinator with controlled conditions; the second one consisted in hydroponic plant cultivation and evaluated physiological parameters of growth, such as length and dry mass of shoot and root, and length and total dry mass. A completely randomized design was adopted in both experiments, being the second one in a split-split plot arrangement. Cu concentrations did not affect seedling establishment capacity, on the other hand the vigor of the seed sub lot affected this ability, with more vigorous (not aged) seeds sub lot having a better establishment. Cu concentrations were detrimental to the initial growth of black oat plants above 60 μM independent of sub lot studied. Seedlings from the non-aged sub lot (high vigor) presented higher initial growth than those from the aged sub lot (low vigor), however acclimatization in the hydroponic system equaled them in root growth and caused an inversion in the total plant growth, being this higher in low vigor sub lot plants.